Convective turbulent dust emission (CTDE) observed over Horqin Sandy Land area and validation of a CTDE scheme. Issue 16 (29th August 2014) - Li, X. L.; Klose, M.; Shao, Y.; Zhang, H. S.
Abstract In this paper, a data set obtained from a sandstorm monitoring station located in Horqin Sandy Land area in northern China from December 2010 to November 2011 is used to investigate the seasonal variations and characteristics of convective turbulent dust emission (CTDE) and to validate a CTDE scheme. The observations show that CTDE events occur during the local daytime, with 85% of them between 08:00 and 15:00 local standard time. While a CTDE event may last for 0.5 to 8 h, the duration of 79% of the events is shorter than 3 h. CTDE occurs most frequently in summer and then in fall, less frequently in spring, and least in winter. The total CTDE flux in the year (=1.63 × 104 µg m−2 s−1) is considerable and important to the background dust concentration and dust cycles from the view of a longer time scale. The CTDE dust flux, Fobs, falls into the range of 0–30 µg m−2 s−1 and is positively correlated with the convective scaling velocity, w*, but not so much with the friction velocity, u*. A CTDE event was observed on 14 October 2011, which lasted for 7 h with a maximum of Fobs = 9.4 µg m−2 s−1. This event is used to validate the CTDE scheme. A linear relationship between the predicted and the observed CTDE dust fluxes is found, and an important model parameter is calibrated for this sandy land.